Power division in the sacred world: the Cults of Neak Ta and Arak of the ethnic Khmer in Southeastern region, Vietnam - Tu Anh Phan (Culture and religion, 2023)
Neak Ta and Arak are two indigenous beliefs which have existed together in traditional Khmer spirituality. This article presents the results of fieldwork in Lộc Khánh commune, Lộc Ninh district, Bình Phước province (about 200 km. north of Hồ Chí Minh City) where Khmer people have continuously maintained their traditional social structure including their strong local beliefs in spiritual power. Using qualitative research methods in combination with document analysis, the article shows that Neak Ta is representative of male power that is confirmed by the power and position of the elder council of the village, while Arak is representative of the female power that is displayed only through a woman appointed by the village clan that controls Arak from a theoretical power clan in the village. As result, it is analysed and examined the link of the theocratic power of Neak Ta and Arak through the rituals and the spirit mediumship in Lộc Khánh commune all which is a positive consequence of gender power balance between patriarchy and matriarchy.